Comparative CFD Analysis of Air–Fuel Ratio Effects on the Performance of a Non-Premixed Combustion Burner - Taufik Kurniawan; Muhammad Ikhlas; Mohammad Zaini Ma'ruf (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
Checker bricks in regenerative furnaces gradually accumulate deposits from glass raw materials during long-term operation, reducing heat transfer efficiency and obstructing combustion air and exhaust gas flow. These deposits increase furnace pressure, accelerate checker brick degradation, and shorten furnace service life. This study evaluates the performance of a non-premixed combustion burner for checker brick maintenance. Computational Fluid Dynamics (CFD) simulations were conducted using the non-premixed combustion model in ANSYS Fluent with different air-to-fuel ratios (AFR) and validated experimentally. The optimum performance was achieved at an AFR of 10.6:1, producing a maximum flame temperature of 944°C and a flame length of 1,683 mm, satisfying the required heating temperature and flame penetration for effective deposit removal. Experimental validation showed stable burner operation at air damper openings between 55% and 60%, successfully melting deposits on the checker brick surface. The proposed burner is suitable for regenerative furnace maintenance, while the validated CFD model provides a reliable approach for future burner optimization and heating coverage analysis of checker brick treatment.